Experimental and Numerical Characterization of Interlaminar Properties of SWCNTs Doped PAN Nano-mats Strenthened Multiscale Hybrid Composites - Arif, Muhammad (My University, 2019)
Polymer composite reinforced with conventional macro size bres have taken a major role in various modern engineering applications and their demand is ever increasing due to their light weight and design exibility. Various im-provements in manufacturing methods, fabrication techniques and composite constituents have been made over the years to produce better polymer com- posites. However, the major challenge of the conventional polymer composites is that failure at the matrix rich interlaminar region still remains and limits their performance resulting in unreliable usage of these composites. A number of research attempts had little success due to various limiting factors have been carried out to rectify this problem. One of the potential methods expected to improve the strength of the interlaminar region is the incorporation of nano-size llers, such as electrospun Polyacrylonitrile (PAN) nano bres mat as an interalia into the matrix rich interlaminar region of the conventional polymercomposite. However, controlling the alignment and distribution of the PAN nano bres during the chaotic electrospinning process is a major hurdle for im-proving the interlaminor regions. The random orientation of electrospun PAN nano bres mat reduces their strengthening e ect and also the required material properties.Hence, the current study has focused on the design of electrospinning process for improving the orientation and distribution of the PAN nano bre mats. The developed electrospinning process was used to produce random and aligned PAN nano bres mat and also used for producing both pristine and function-alized single walled carbon nanotubes (SWCNTs) doped PAN nano bres mat. These nanomats were then sandwiched with the glass bre-epoxy matrix to produce nano strengthened multiscale hybrid composites. As part of the electrospinning procedure, electric elds of general electrospin- ning technique were manipulated using two position adjustable auxiliary ver- tical electrodes (AVEs) to produce aligned nano bres mat along with reduced diameter. So as to optimise the electrospinning parameters, the e ect of AVEs on the PAN nano bres mat orientation, distribution and diameter were ex- perimentally matrixed and analysed. The fractographic study showed that auxiliary vertical electrodes (AVEs) added to the electrospinning process re- duced the diameter, enhanced the alignment of the nano bres and improved molecular orientation. Among four di erent volume fractions of 0.1%, 0.2%, 0.5% and 1% randomly oriented PAN nano bre mats, the volume fraction of 0.5% PAN polymer was selected to manufacture aligned PAN nano bres mat strengthened hybrid composite based on the improved experimental randomly oriented PAN nano bre mats strengthened hybrid composites. A series of tests showed that glass bre composites (GFC) reinforced with the volume fraction of 0.5% aligned nano bre mats were better than those of 0.5% randomly distributed nano bre mats. The aligned nano bre mat with reduced diameter increased the tensile, exural, and impact properties of glass bre composite by 68.91%, 95.32% and 45.30% respectively. Aligned nano bres mat was further utilised to align and disperse the pristine and functionalized SWCNTs into the interlaminar region of breglass compos- ite. Alignment and a nano-range diameter of nano bres helped in improved distribution and alignment of pristine SWCNTs (p-SWCNTs), which was re- ected in an increase in tensile, exural and impact resistance by 89.30%, 105.48% and 107.17% respectively. A nondestructive functionalization method (Friedel craft alkylation) was used to improve the interface bonding of SWC- NTs with the host PAN polymer nano bre. PVA chains crafted to the surface of the SWCNTs without damaging the wall was con rmed using FTIR and Ra- man spectroscopy. The e ect of functionalized SWCNTs (f-SWCNTs) doped aligned PAN nano bre mats improved the properties of nano-hybrid multiscale composite up to 111.34%, 117.11% and 180.03% in tensile, exural and impact resistance respectively. A multiscale model was used to determine the properties of the multiscale nanohybrid composite strengthened with random and aligned PAN nano bre mats, PAN doped with p-SWCNTs and f-SWCNTs aligned nano bre mats. Three length scales, such as nano, micro and macro scales were modelled. At rst, a numerical model was developed to determine the elastic properties of di erent carbon nanotubes (CNTs) i.e. Pristine and defective single wall (SWCNTs), double wall (DWCNTs), and multiwall (MWCNTs) for zigzag and armchair con gurations. CNTs atomic geometry was replicated with an equivalent space frame structure (SFS). Co-ordinates de nition of SFS of CNTs was developed in MATLAB code and transferred to the nite element analysis (FEA) software 'ANSYS'. The basic entity of SFS, C-C chemical bond was designed as a circular beam of orthotropic properties. The properties were determined by linking the energy equation of molecular mechanics to structural mechanics along with the parametric study. The van der Waals forces between inter-shell of DWCNTs and MWCNTs were modelled as linear elastic springs in a simpli ed way. The simpli ed model avoided the problems due to the nonlinear behaviour of van der Waals forces and improved the performance of the FEA software by computational resources. The e ect of chirality, vacancy defects, di erent diameters and numbers of walls on elastic properties of CNTs were calculated, tabulated and compared with each other. The result of the proposed SFS model with orthotropic properties was compared with others result. The SFS model is found better than the equivalent shell model as the defects can be placed at the exact location and a more realistic behaviour could be predicted. The SFS models could be developed with any type of defects, a number of walls, van derWaals and agglomerated forms with variable geometries. Using the space frame structures (SFS) of SWCNTs, the nanoscale RVE of PAN nano bre doped with SWCNTs was modelled. Simulated results of nanoscale RVEs were used to determine the equivalent properties of p-SWCNTs and f-SWCNTs doped nano bres, which were further used in microscale RVE models. Four micro scale RVEs were developed to represent the random and aligned PAN nano bres mats, PAN nano bres mat doped with p-SWCNTs and f-SWCNTs aligned PAN nano bres mat in epoxy matrix. Analysed micro scale RVEs provided equivalent properties of interlaminar regions developed with random and aligned PAN nano bres mat, PAN doped with p-SWCNTs and f-SWCNTs aligned nano bres mat. At the macro scale, MNHCs were de- veloped with equivalent interlaminar regions and analysed. The results of the simulated MNHCs were compared with experimentally obtained results. The results of the experimental study suggested that aligned nano bres with reduced diameter improved the properties of interlaminar region noticeably than the random nano bres mat of the same volume fraction. Aligned nano - bres successfully placed the pristine and functionalized SWCNTs within the multiscale hybrid composites which signi cantly improved the properties of the multiscale hybrid composite. Results of the multiscale modelling were in line with the experimental results, which could be useful in extending the small- scale theoretical results to the real-life applications.
project report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial ful lment of the requirements for the degree of Doctor of Philosophy(PhD). Date: 15th May 2019
Keywords: Fibrous composites; Nanostructured materials; Nanoparticles